Effect of OATP1B1/1B3 Inhibitor GDC‐0810 on the Pharmacokinetics of Pravastatin and Coproporphyrin I/III in Healthy Female Subjects. (22nd May 2018) - Liu, Lichuan; Cheeti, Sravanthi; Yoshida, Kenta; Choo, Edna; Chen, Eugene; Chen, Buyun; Gates, Mary; Singel, Stina; Morley, Roland; Ware, Joseph; Sahasranaman, Srikumar
Abstract: Developed as an oral anticancer drug to treat estrogen receptor–positive breast cancer, GDC‐0810 was shown to be a potent inhibitor of organic anion‐transporting polypeptide 1B1 and 1B3 (OATP1B1/1B3) from an in vitro assay. A clinical study was conducted to assess the drug‐drug interaction potential between GDC‐0810 and pravastatin, which is a relatively selective and sensitive OATP1B1/1B3 substrate. Fifteen healthy female subjects of non‐childbearing potential were enrolled in the study. On day 1 in period 1, a single 10‐mg dose of pravastatin was administered to all subjects. Following a 4‐day washout period, 600 mg of GDC‐0810 was administered once daily on days 5 through 8 in period 2 to achieve steady‐state concentrations. On day 7, a single dose of 10‐mg pravastatin was coadministered with the 600‐mg GDC‐0810 dose. Concentrations of pravastatin (periods 1 and 2) and GDC‐0810 (period 2 only) were quantified in blood samples and subsequently used to calculate the pharmacokinetics (PK) parameters. The pravastatin mean maximal concentration and area under the curve values were approximately 20% and 41% higher, respectively, following pravastatin coadministration with GDC‐0810 compared to pravastatin alone. Based on the magnitude of change in this drug‐drug interaction study, dose adjustments for pravastatin (and other OATP1B1/1B3 substrates) were not considered necessary when administered with GDC‐0810. Retrospectively, the endogenous biomarkers of OATP1B1/1B3, coproporphyrin I and III, were also measured and showed changes comparable to those of pravastatin, indicating their utility in detecting weak inhibition of OATP1B1/1B3 in the clinical setting.